1998
DOI: 10.2118/98-05-04
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Immiscible Oil And Water Flow In a Smooth-walled Fracture

Abstract: Steady state immiscible oil/water flow experiments were conducted in horizontal smooth-walled fractures. The effects of fracture aperture, injection rate and injection method on the immiscible flow characteristics were investigated. The experimental data were analysed using a porous medium approach and an equivalent homogeneous single-phase method. The pressure gradients predicted by the latter are in good agreement with those measured in the experiments. Contrary to the well-known Romm's relative permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Due to the interfacial coupling effects, k rw + k ro is always lower than unity, meaning that the resistance of two‐phase flow is larger than that of single‐phase flow in porous media. Similar results have been observed for two‐phase flow in purely wet porous media (Bertels et al, ; Pan et al, ; Pruess & Tsang, ). The lower the sum of relative permeability, the larger the flow resistance.…”
Section: Resultssupporting
confidence: 86%
“…Due to the interfacial coupling effects, k rw + k ro is always lower than unity, meaning that the resistance of two‐phase flow is larger than that of single‐phase flow in porous media. Similar results have been observed for two‐phase flow in purely wet porous media (Bertels et al, ; Pan et al, ; Pruess & Tsang, ). The lower the sum of relative permeability, the larger the flow resistance.…”
Section: Resultssupporting
confidence: 86%
“…Owing to the lack of experimental data, Romm's linear correlation has been widely used in fractured reservoir simulations. Results from recent laboratory experiments of oil‐water flow in parallel‐plate models [ Merril , 1975; Pan et al , 1998] indicated that under a viscous force controlled condition, the interference between two phases flowing concurrently in a fracture could be strong at high flow rates. At intermediate saturations, the sum of wetting and nonwetting phase relative permeability values was found to be much less than unity.…”
Section: Introductionmentioning
confidence: 99%
“…The Reynolds number [27,28], Re, for the flow of well liquid in the wellbore and the draught loss, s, caused by the flow through pump valve can be given by:…”
Section: Design Calculation Of Friction Loadingsmentioning
confidence: 99%